LA PRODUCCIÓN SOCIAL DE VIVIENDA A TRAVÉS DE LA PRÁCTICA ASOCIATIVA EN SIETE PAÍSES SUDAMERICANOS (Revista cientifica In Vestigium Ire, 2016)
The length and width of the continent, people with common needs and objectives have associated in different organizational forms. This is a practice that involves grouping people who voluntarily agree to common objectives; undertake to comply with the internal rules of ethics in accordance with your self-government, to make democratic decisions and to working together, these associations are in charge of solving meeting individual and collective needs. The aim of this article is to know the different associations involved in the creation of social housing, beginning with an informal experience involving an interesting case in Peru, and following with the formal experiences of housing associations in seven South American countries: Brazil, Colombia, Argentina, Peru, Venezuela, Chile and Uruguay. Taking this aim into account, this article is organized around a brief conceptualization of the creation of social housing and associative practices. It then makes a summary of the history of housing associations and the stages involved in converting from an informal association to a formal one. Finally, it presents the types of association in the seven aforementioned South American countries.
Keywords: Associative practice; organization; housing; car production and formal and informal